2019
DOI: 10.1186/s12986-019-0376-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dicarbonyl stress on the development of kidney dysfunction in metabolic syndrome – a transcriptomic and proteomic approach

Abstract: Background and aims Dicarbonyl stress plays an important role in the pathogenesis of microvascular complications that precede the formation of advanced glycation end products, and contributes to the development of renal dysfunction. In renal cells, toxic metabolites like methylglyoxal lead to mitochondrial dysfunction and protein structure modifications. In our study, we investigated the effect of methylglyoxal on metabolic, transcriptomic, metabolomic and proteomic profiles in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Upregulated Lpin1 positively affects triglyceride biosynthesis control in the endoplasmic reticulum, while Nr1d1 regulates lipid metabolism by influencing SREBPs and PPARα. On the other hand, downregulated Lrpap1 , which encodes a protein that interacts with LDL receptors, is involved in the alteration of circulating lipids, as observed after MG exposure in our study [ 18 ] and in others [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Upregulated Lpin1 positively affects triglyceride biosynthesis control in the endoplasmic reticulum, while Nr1d1 regulates lipid metabolism by influencing SREBPs and PPARα. On the other hand, downregulated Lrpap1 , which encodes a protein that interacts with LDL receptors, is involved in the alteration of circulating lipids, as observed after MG exposure in our study [ 18 ] and in others [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 70%
“…However, serum adiponectin levels ( Table 1 ) and skeletal muscle insulin sensitivity (data not shown) in MG-treated rats were not different to controls. While MG administration increased adrenaline-stimulated lipolysis ( Figure 1 B), NEFA concentrations only increased slightly [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MG treatment inhibited the insulin receptor pathway in 3T3L1 adipocytes [30,31] and pancreatic cell line INS-1E [32]. One study to treat hereditary hypertriglyceridemic rats (a model of dyslipidemia and insulin resistance) with intragastric administration of MG (0.5 mg/kg body weight for 4 weeks) reported a development in dicarbonyl and oxidative stress associated with reduced glucose tolerance and renal microvascular complications [33]. Another study showed that Sprague-Dawley rats treated with 1% MG in drinking water for 4 weeks were predisposed to diabetes and salt-sensitive hypertension [34].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the anti-oxidative effect of AAV-GR in kidney, we monitored urinary 8-isoprostane concentration, another marker of renal oxidative stress [ [30] , [31] , [32] , [33] ], at different time points after AAV-GR delivery. A significantly higher urinary level of 8-isoprostane was found in KL +/– mice versus WT mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%